Training and Practice of Recreational Sports Education Models for Students with Intellectual Disabilities based on Flipbook for Physical Education Teachers - Burhaein, Erick; Arisyanto, Prasena; Ardiyanto, Asep; Melinda, Erika Trisna; Firmansyach, Heidi Wildan; Udhiyah, Itsna; Rohimah, Rohimah; Yulianingsih, Nasrifah; Ikhsani, Assifa Luffi (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
Background: A gap in adapted physical education services for children with mild intellectual disabilities remains a challenge, particularly in terms of teachers' ability to design engaging and meaningful lessons.Aims: This community service activity was carried out in collaboration with KKG SLB Kebumen with the aim of improving the competence of physical education teachers through training in adventure education-based learning models using digital flipbook modules.Method: The program was implemented in five stages, namely socialization, training, technology application, mentoring, and sustainability. The flipbook module contains four educational games Ambenbol, Bowna, Spomas, and Lampubol designed to develop motor, communication, and socio-emotional skills of children with mild intellectual disabilities.Results: The pretest–posttest results showed a significant improvement in four aspects of teacher competency: adaptive learning design (increased by 25%), application of game-based learning (25%), motor development evaluation (22%), and utilization of digital technology (37%).Conclusion: These findings indicate that the use of flipbooks can strengthen teachers' creativity and increase student participation in adaptive physical activities. This activity contributes to improving the quality of inclusive learning in special needs schools and serves as a model for continuous training for physical education teachers in various regions. A follow-up program is recommended to expand the use of interactive technology and strengthen the collaborative network between inclusive schools.